2016
DOI: 10.1093/heapol/czv138
|View full text |Cite
|
Sign up to set email alerts
|

The individual level cost of pregnancy termination in Zambia: a comparison of safe and unsafe abortion

Abstract: Zambia has one of the most liberal abortion laws in sub-Saharan Africa. However, rates of unsafe abortion remain high with negative health and economic consequences. Little is known about the economic burden on women of abortion care-seeking in low income countries. The majority of studies focus on direct costs (e.g. hospital fees). This article estimates the individual-level economic burden of safe and unsafe abortion care-seeking in Zambia, incorporating all indirect and direct costs. It uses data collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 42 publications
4
45
0
Order By: Relevance
“… 11 Economic and social costs are high, and the procedure is strongly socially stigmatised. 12 Women must often travel long distances to reach a health facility that can provide the procedure. There is a shortage of health providers: in Central Province, where our study took place, there is one medical doctor for every 111 648 people.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Economic and social costs are high, and the procedure is strongly socially stigmatised. 12 Women must often travel long distances to reach a health facility that can provide the procedure. There is a shortage of health providers: in Central Province, where our study took place, there is one medical doctor for every 111 648 people.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is approximately in line with study done in Zambia (39%). [14] However, it is lower than the finding of study conducted in Ghana (64.1%) and higher than the finding of study conducted in Mexico (16.5%). [12,25] The difference might be due to the economic inequality, educational level of women, and abortion policies of these countries.…”
Section: Discussionmentioning
confidence: 59%
“…Study conducted by Tiziana Leone also reported that poor women are more likely to practice unsafe abortion. [14] Study conducted in Mexico also revealed that socio-economic gradients have a significant association with practicing unsafe abortion, which means poorer women are more likely to have unsafe induced abortion than wealthy women. [12] So, women's economy level play important role in the health and outcomes of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, legal abortion services have not been widely available in health centers or hospitals, compelling women to continue to turn to illegal providers and unsafe methods and confirming that just the existence of a law, with insufficient political will or guidance for implementation may not be effective in improving maternal health [ 6 , 10 12 ]. Unsafe abortion – the termination of an unintended pregnancy either by persons lacking the necessary skills or in an environment lacking the minimal medical standards, or both – contributes to 8-13% of global maternal mortality [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%